6×6 Array of Four-arm Spiral Antennas for High-gain Satellite Receiver Applications at Low Elevation - Amit Mehta (2018 IEEE International Symposium on Antennas and Propagation & USNC/URSI National Radio Science Meeting, 2018)
A 6×6 array of four-arm spiral antennas is presented for satellite receiver applications at 18 GHz. The array provides a wide-angle elevation scanning with a high gain right handed circularly polarized (RHCP) radiation beam. Each spiral element has four spiral arms with four feeding ports. The four arms are arranged symmetrically with respect to the center of the antenna. When one of the four ports are excited and other ports are open-circuited, the spiral element provides an RHCP tilted beam (θ max = 51°) with a gain of 8.4 dBi. By switching the excitation among the four feeding ports, the spiral element can switch the beam in four different quadrants in space. It is demonstrated that by combining these four unit-patterns, the 6×6 array of four-arm spirals provides an elevation scanning range of -70°≤ θ ≤ 70° with a maximum gain up to 20.6 dBi.